The validation of a three-dimensional ball rotation model - Whiteside, D.; Chin, A.; Middleton, K. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2013)
With the development of three-dimensional motion analysis systems, methods for accurately tracking and modelling three-dimensional body kinematics have evolved and are well established. Comparatively, the methodologies involved in tracking ball flight have failed to utilize three-dimensional motion analysis, hence this proposal of a new model. A 12-camera VICON MX motion analysis system captured the kinematics of three sports balls rotating on the end of a drill. The balls were positioned in three orientations and spun at three speeds in each. Comparing differences between: (a) the modelled spin axis of the ball with that of the fixed drill bit about which it was rotating, and (b) the rotation rate of the modelled ball with the stable waveform of a marker thereon, revealed the validity of the proposed ball model. These differences were found to be minimal, suggesting that the proposed ball model is an advancement of its predecessors.